2015
DOI: 10.1021/acs.joc.5b00923
|View full text |Cite
|
Sign up to set email alerts
|

Development and Application of O-(Trimethylsilyl)aryl Fluorosulfates for the Synthesis of Arynes

Abstract: A class of o-(trimethylsilyl)aryl fluorosulfates was synthesized by a concise method and successfully used as aryne precursors for the first time. Different trapping agents such as azides, furans, and acyl acetoacetates could successfully react with the aryne precursors under mild conditions with good to excellent yields.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 62 publications
1
22
0
Order By: Relevance
“…[29,30] Fluorosulfonates, also known as "super sulfates," were first reported more than four decades ago, [31][32][33][34][35][36] their chemistry, however, is relatively unexplored. [29,30] Fluorosulfonates, also known as "super sulfates," were first reported more than four decades ago, [31][32][33][34][35][36] their chemistry, however, is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…[29,30] Fluorosulfonates, also known as "super sulfates," were first reported more than four decades ago, [31][32][33][34][35][36] their chemistry, however, is relatively unexplored. [29,30] Fluorosulfonates, also known as "super sulfates," were first reported more than four decades ago, [31][32][33][34][35][36] their chemistry, however, is relatively unexplored.…”
Section: Introductionmentioning
confidence: 99%
“…has been successfully applied in the construction of C(sp 2 )ÀC and C(sp 2 ) À Nb onds. [10] SO 2 F 2 has also been applied in the production of the important yet expensive bis(fluorosulfuryl)imide anion for the new-generation electrolyte in lithium ion batteries. [11] Although SO 2 F 2 possesses ideal reactivity and selectivity as aS uFEx connector,i te ncountered several challenges as areagent for use in research laboratories.First, operations are problematic for those laboratories without sufficient apparatus to handle harmful gas or under strict regulations to acquire SO 2 F 2 .S econd, compared with phenols,S O 2 F 2 reacted sluggishly with secondary amines to generate sulfamoyl fluorides with al imited substrate scope,a nd complicated reaction conditions were required.…”
mentioning
confidence: 99%
“…Wang and co‐workers reported that o ‐(trimethylsilyl) phenyl fluorosulfate ( 150 ) reacted with different azides that contained electron‐donating as well as electron‐withdrawing substituents under their optimized reaction conditions to afford benzotriazoles 151 in good‐to‐excellent yields (Scheme ) . The same group also continued their research to expand the synthetic applicability of this precursor to other types of reactions (Scheme ).…”
Section: Chemical Transformationsmentioning
confidence: 99%